(untitled) (Ustozlar uchun, 2026)
Rapid medical diagnosis and treatment using modern laser technology are becoming increasingly important in medicine and dentistry, thanks to groundbreaking software packages for Raman and fluorescence analysis. The use of broadband, high-energy laser radiation serves a dual purpose: firstly, as a therapeutic tool [1, 2, 3, 4]; and secondly, as a way to enhance the Raman luminescent diagnostic capabilities of a biological sample [5] (in this case, we are referring to biophotometry).